The Beatles Level 3 - Shipton, Paul; Hopkins, Andy; Potter, Jocelyn (England Pearson Education Ltd, 2008)
This book tells the story of the greatest band in the world from the early days in Liverpool to the Beatles' music in the world today.
Keywords: Tham khảo